Social and Educational Exclusion of Roma in Macedonia with Focus on Roma Children on the Street - Bogoevska, Natasha; Trbojevik, Svetlana (Richtmann Publishing, 2012)
Social and Educational Exclusion of Roma in Macedonia with Focuson Roma Children on the Street